Ombudsman Performance Representative Of Bengkulu Province - Presilia Andra Sari Sapitri; Harius Eko Saputra; Yusuarsono Yusuarsono (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the performance of the Bengkulu Province Representative Ombudsman Institution in examining and resolving public complaints reports from various existing cases. This study uses a qualitative descriptive method. Data collection uses observation, interview and documentation techniques. The informants in this study amounted to 6 people, namely the head of the ombudsman, assistant, administration, and reporting. The results of this study show that the performance of the Bengkulu Province Representative Ombudsman has a good performance, based on Bernardin's theory (2000:34) the researcher found that the Bengkulu Province Representative Ombudsman's performance was good even though in terms of human resources that were still lacking, the Bengkulu Province Representative Ombudsman always carried out his duties. professionally and have high motivation and commitment